2018
DOI: 10.1556/004.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of amniotic uric acid, glucose, lactate and creatinine concentrations and lactate/creatinine ratio with newborn survival in small-sized dogs – preliminary results

Abstract: In order to define the normal composition of canine amniotic fluid and to detect differences between surviving and non-surviving newborn puppies, the present study determined the uric acid, glucose, lactate and creatinine concentrations and the lactate to creatinine ratio in amniotic fluids collected during elective Caesarean section from small-sized purebred bitches. The possible relationship between newborn survival and the studied parameters, as well as the effects of maternal parity, fetal gender and Apgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
5
9
0
Order By: Relevance
“…The outcome of the newborns at 24 h of life (alive/dead) according to the distribution of viability classes based on Apgar score showed that 97% of puppies scored 7–10, 96% of puppies scored 4–6 and 39% of puppies scored 0–3 were alive 24 h after birth. When compared to previous studies, the survival rate in puppies scored as 7–10 is in agreement with the 95–100% reported before [ 3 , 13 , 18 20 , 33 ]. Similarly, the survival rate in puppies scored as 4–6 agrees with the 94–100% previously reported [ 18 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The outcome of the newborns at 24 h of life (alive/dead) according to the distribution of viability classes based on Apgar score showed that 97% of puppies scored 7–10, 96% of puppies scored 4–6 and 39% of puppies scored 0–3 were alive 24 h after birth. When compared to previous studies, the survival rate in puppies scored as 7–10 is in agreement with the 95–100% reported before [ 3 , 13 , 18 20 , 33 ]. Similarly, the survival rate in puppies scored as 4–6 agrees with the 94–100% previously reported [ 18 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of 28% referred to the "moderately distressed" puppies is, in turn, higher than the 2-10% reported by [3,13,18], but more similar to the 34-44% reported by Vilar et al [20]. The 10% proportion of "severely distressed" puppies, is higher than the reported 2-4% [3,13], more similar to the 8% reported by [20,33], but markedly lower than then the 43% reported by Titkova and colleagues [18]. Data from the present study showed, therefore, that in Chihuahua dogs born by elective Caesarean section about one-third of the newborns are classified as "less viable" (Apgar score 0-6), despite the timely performed surgery, anesthetic protocol used aimed to minimize side-effects on newborns and bitches, and the prompt evaluation and assistance performed by an experienced neonatologist.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In 2021, Tal et al [ 5 ] demonstrated the possibility to easily and safely perform amniocentesis in anesthetized bitches at around 35–62 days of pregnancy. Moreover, at the time of parturition, when caesarean section is performed, fetal fluids (amniotic and allantoic) can be easily and securely sampled, as demonstrated by many studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Other than that, the canine fetal fluids were also useful for mesenchymal stem cells isolation and growth as a model of these cell’s biology study and for possible therapeutic application [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a hormonal standpoint, canine fetal fluids collected along pregnancy during ovariohysterectomy have been studied also to possibly assess the beginning of thyroid gland function in canine fetuses through the measurement of thyroid hormones [ 21 ] and for a better understanding of the fetal endocrine system development [ 22 ]. Among the biochemical composition of canine amniotic and allantoic fluids, some studies [ 10 , 14 ] have suggested that amniotic glucose concentrations were associated to the puppies’ outcome. One study [ 14 ] reported the finding of a higher concentration of glucose in surviving than non-surviving puppies, demonstrating the relevance of measuring glucose in amniotic fluid to identify newborns with a higher risk of demise after parturition.…”
Section: Introductionmentioning
confidence: 99%